Corporate governance and strategic human resource management: Four archetypes and proposals for a new approach to corporate sustainability. Issue 1 (February 2016) - Martin, Graeme; Farndale, Elaine; Paauwe, Jaap; Stiles, Philip G.
Abstract: In this paper we develop a new typology connecting strategic human resource management (SHRM) to different models of firm-level corporate governance. By asking questions concerning ownership and control issues in the corporate governance literature and drawing on institutional logics, we build a typological framework that identifies four firm-level archetypes of corporate governance systems. Two archetypes represent dominant logic types (shareholder value, communitarian stakeholder), while the other two represent hybrid organizations (enlightened shareholder value, employee-ownership). Using these archetypes, we theorize the implications of different governance structures for SHRM and the challenges they pose. We conclude by discussing a novel solution to many of these challenges based on the corporate sustainability literature, and, in so doing, provide new directions for SHRM research to tackle key challenges facing organizations and the management of people.